2021
DOI: 10.1136/bmjgast-2021-000695
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia, sepsis and antibiotic resistance in Australian patients with cirrhosis: a population-based study

Abstract: ObjectiveMultiple factors predispose patients with cirrhosis to sepsis and/or bacteraemia and this has a high mortality rate. Within different geographical regions there are marked differences in the prevalence of infection with multidrug-resistant organisms (MDR). This study examined risk factors for and outcomes of sepsis/bacteraemia in public hospital admissions with cirrhosis in the state of Queensland, Australia, over the last decade, along with the bacterial pathogens responsible and their antibiotic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…However, a recent retrospective cohort study has demonstrated a low prevalence of MDRO in blood cultures of patients with cirrhosis hospitalized in Australia (5.6% of admissions). Despite the low prevalence, the study has shown a significant increase in infections caused by MDRO over a decade[ 18 ], similarly to what had been previously verified in Europe[ 10 ].…”
Section: Epidemiologysupporting
confidence: 58%
See 1 more Smart Citation
“…However, a recent retrospective cohort study has demonstrated a low prevalence of MDRO in blood cultures of patients with cirrhosis hospitalized in Australia (5.6% of admissions). Despite the low prevalence, the study has shown a significant increase in infections caused by MDRO over a decade[ 18 ], similarly to what had been previously verified in Europe[ 10 ].…”
Section: Epidemiologysupporting
confidence: 58%
“…, hospitalization or short-term admission for at least 2 d in the previous 90 d, residence in a nursing home or a long-term care facility, or chronic hemodialysis) and community-acquired infections (20% and 0%, respectively)[ 22 ]. Similarly, an intercontinental study evaluated 1302 infected cirrhotic patients and confirmed that infections caused by MDRO were associated with a lower efficacy (40% vs 68%) and a longer duration (12 d[ 7 - 18 ] vs 10 d[ 7 - 15 ]) of empirical antibiotic treatment. Furthermore, patients with bacterial infections by multi-resistant strains had a higher incidence of septic shock (27% vs 13%) and higher in-hospital and 28-d mortality rate (31% vs 21% and 34% vs 22%, respectively)[ 7 ].…”
Section: Prognostic Impact Of Multidrug Resistant Bacterial Infectionsmentioning
confidence: 85%
“…We recently reported on the incidence of bacteremia, sepsis and antibiotic resistance to bloodstream infections in the same cohort analysed here. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported on the incidence of bacteremia, sepsis and antibiotic resistance to bloodstream infections in the same cohort analysed here. [30] Infection in AF, including SBP and bacterascites, is one of the most common infections in patients with cirrhosis and is associated with 18% to 40% in-hospital mortality. [31] We observed a relatively high in-hospital mortality rate in SBPpositive (28%) compared to SBP-negative admissions, but report a significant decrease in in-hospital morality over the 10-year study period.…”
Section: Discussionmentioning
confidence: 99%
“…Once sepsis occurs in patients with liver cirrhosis there is a significant increase in short and long-term mortality 13 . Also in-hospital mortality is significantly higher [27.7% (26.3–29.1%) vs. 3.7% (3.6–3.8%)] 14 . Although more studies exist on sepsis in the past, there is still a lack of research on sepsis in patients with cirrhosis 15 .…”
Section: Discussionmentioning
confidence: 98%